Elastic lateral-torsional instability of monosymmetric shear deformable fixed arches under a localized uniform radial load. (March 2021) - Liu, Lulu; Lu, Hanwen; Liu, Airong; Pi, Yong-Lin; Bradford, Mark Andrew; Huang, Yonghui; Fu, Jiyang
Abstract: This paper investigates the elastic lateral-torsional instability of shear deformable fixed arches having a monosymmetric cross-section when subjected to a localized uniform radial load. Hitherto, this topic has not been addressed in the open literature. The complex in-plane internal actions in a fixed arch with a monosymmetric section are produced by a localized uniform radial load and are affected by the arc length of localized load segment. When the in-plane internal actions reach certain magnitudes, the fixed arch may fail suddenly in a lateral-torsional instability mode. The lateral-torsional instability loads of such arches considering shear deformations under a localized uniform radial load are difficult to obtain and are investigated in this paper. The strain-displacement relationships for the longitudinal normal axial and shear strains in the arch with a monosymmetric section are derived. In-plane analyses for the internal forces produced by the localized uniform radial load are firstly carried out. The analytical solution for the lateral-torsional instability load accounting for shear deformations and monosymmetry is then obtained using the principle of stationary potential energy together with the Rayleigh-Ritz method and compared with ANSYS numerical results. It is found that the monosymmetry parameter, the shear deformations, the slenderness ratio and the arc length of the localized load segment have considerable effect on the lateral-torsional instability load of fixed arches with a monosymmetric section. Highlights: Lateral-torsional instability load of monosymmetric arch with out-plane fixed boundary conditions are obtained. Investigation of lateral-torsional instability for a monosymmetric arch under the localized uniform radial load . The first mode instability deformations of monosymmetric arch can be simulated by the three terms of the Fourier series. Influence of monosymmetry parameter on the instability load of I-section arch is more obvious than that of box-section arch. Influence of shear deformations on the instability load of box-section arch is more obvious than that of I-section arch.